A descriptive study of access to psychological assessment materials on-line: How accessible are images of commonly used cognitive and personality tests? - Brad A. MacNeil; Grace Fitzgibbons; Chandler Gotfried; Lauren Kraft; Parker Krain; Melisa Mendoza; Chloe Parr; Isabella Savage; Olivia Wilkerson (Acta Psychologica)
The protection of psychological tests is important. The potential for open access to protected test materials on the internet represents a new concern. In this exploratory study, we examined access to images of commonly used cognitive and personality test materials on the internet. We also examined the content of the images that were accessible, whether test stimuli or sample stimuli were present, and the online posting source. An internet image search was conducted using keywords to determine web-based access to cognitive and personality test materials. Results demonstrated easy access to images of many commonly used cognitive and personality test materials through an online image search. Images included test record forms, and in some cases actual or sample test items and stimuli. Common sources where the images were posted online included social media, research and private practice websites. Results from this exploratory study provide initial helpful insights into the access to images of psychological test materials online, and safeguarding considerations for psychologists, other professionals, and test publishers working to protect the integrity of these tests.